Using single nucleus RNA-seq to determine the effect of immunosuppression on the transcriptional activity of resident CNS cells in a mouse model of CNS-TB - Amien, Ilyaas (Department of Human Biology, 2025)
Tuberculosis (TB) is the leading infectious cause of death worldwide and is particularly prevalent in South Africa. Central Nervous System TB (CNS-TB), specifically TB Meningitis (TBM) is the deadliest complication of the disease. Given the high co-prevalence of HIV and CNS-TB, many transcriptional studies have examined the immunocompromised response to CNS-TB, but none have done so atsingle cell resolution. Single nucleus RNA Sequencing (snRNA-seq) was used to determine the effect of immunosuppression on the transcriptional activity of resident CNS cells in a mouse model of CNS-TB. The model consisted of two mouse genotypes, namely Wildtype and TNF knockout (TNF-/- ). Mycobacterium Tuberculosis was injected into the somatosensory cortex of the treatment groups, with control samples receiving a saline injection. Brains were harvested at 9- and 17-days post inoculation. Following library generation, removal of ambient RNA and data processing using Seurat, differential gene expression analysis was used to identify differentially expressed genes (DEGs). Oligodendrocytes had the most DEGs in the general TB response, whereas excitatory neurons had the highest DEGs in the immunocompromised TB response and with disease progression. Potential mechanisms by which these cell types contribute to the pathogenesis of CNS-TB were explored, such as excitotoxicity, demyelination and neurodegeneration. Pathways related to neurogenesis were identified in the immunocompromised TB response. The study adds to the body of knowledge by identifying cell type specific resident gene expression responses in the context of CNS-TB.